Engagement to collaborative learning in formal and informal learning activities / Wan Siti Atikah Wan Omar and Siti Suhaila Harith - Wan Omar, Wan Siti Atikah; Harith, Siti Suhaila (2013)
Learning styles in higher education nowadays become more challenging and demanding. Collaborative learning is also part of learning style that students should consider when involving in group activities or engaging learning activities beyond individual range. As some learning activities may need individual self effort and self-intellectual merit. collaborative learning may contribute to benefit others especially among peers or colleagues. As suppose this mutual relationship grants lot of extra improvement on one 'soft skills and upbringing leadership, some cases of engaging collaborative learning are difficult to handle. Learning also include the informal activities that one associate in his/her daily life or as students' life. In this paper, we will discuss on some learning activities that show engagement on collaborative learning as informal and informal learning and also common problems in such activities. It is believed that learning activities in any engagement should be enjoyable and yet enlightening the value of knowledge.